Nothing Like a Good Fiasco! Exploring the Potential of Tabletop Role-Playing Games (TRPGs) As Literacy Experiences - Harrison Campbell; Andrea Madsen (Canadian Society for Studies in Education, 2021)
Within this position paper, we describe the use of Fiasco, a tabletop role-playing game (TRPG), as it relates to the creation of literacy experiences. Fiasco is a TRPG that utilizes prompts inspired by genre fiction to collaboratively generate, establish, and resolve scenes between a varied cast of characters in several rounds improvisational roleplay. To explore the range of literacy experience opportunities, present in its play, we present our experiences designing and playing a Fiasco session and reflect upon the transformative potential of tabletop games in creating literacy experiences. The position we undertake, in favor of the considered use of TRPGs for learning through serious gaming in classrooms, is reflective of the experiences within our local gaming and learning communities. Based upon this experience and relevant literature, we contend that table-top gaming fits well within literacy pedagogy and explore how they can be used in classrooms. Therefore, our discussion is centered upon the potential of tabletop games experiences to be considered inventive, specifically in relation to the teaching and learning of literacy skills within a serious gaming framework.